Bioleaching and chemical leaching of magnesium from serpentinites (Zlatibor Mt. ophiolite massif, Serbia) with potential application in mineral carbonation process for CO2 sequestration - Stanković, Srđan; Atanacković, Nebojša; Štrbački, Jana; Kovač, Sabina; Šarić, Kristina; Nikšić, Đurica; Schippers, Axel (Frontiers in Microbiology, 2025)
Magnesium (Mg) extraction via leaching of serpentinite rocks from of the ultramafic massif of Zlatibor Mountain, Serbia, could be applied in mineral carbonation processes for permanent CO2 sequestration. Four different Mg leaching approaches were experimentally tested: (1) sulfuric acid leaching in chemical reactors, (2) bioleaching with the sulfur-oxidizing bacteria Acidithiobacillus thiooxidans in bioreactors, and (3) simulated heap leaching of coarse rock particles in percolators with both, chemical and biological methods. Experimental results show that bioleaching in bioreactors and leaching with sulfuric acid were most efficient with Mg leaching degrees of 95 ± 3.9% and 92 ± 2.8%, respectively. Bioleaching and leaching with sulfuric acid in percolators was less efficient, with Mg extractions of 16 ± 1.4% and 73 ± 2.9%, respectively. This study proposes new pathways for the development of cost-effective, scalable solutions for mitigating climate change using abundant ultramafic rock resources.